Expression of defensins in the jejunum of newborn alpacas (Vicugna pacos) with enteropathies - Siuce M., Juan (2015)
The aim of this study was to determine the expression of antimicrobial peptides (α- and β-defensins) in the intestinal epithelium of newborn alpaca (1 to 6 weeks of age) with enteropathies, using the relative quantification of messenger RNA (mRNA) of the α (Defa 8) and β (β def alp) defensins. Two portions of the jejunum (2 cm) were collected from 29 newborn alpaca with signs of diarrhea. One portion was processed for histological analysis using hematoxylin-eosin staining to determine the type of enteropathy. The second portion was used to obtain total mRNA from jejunal scrapings, which served as template for cDNA synthesis by reverse transcription (RT), followed by a Real-Time PCR for the amplification and detection of defensins. The relative quantification of mRNA was performed using 2-ΔΔCt method. The sick newborn showed an expression of α-defensin (Defa 8) corresponding to 18.15 times as expressed by the newborn animal or calibrator and the expression ofβ-defensin (β-def alp) corresponded to 258.29 times as expressed by the calibrator. Statistical difference was found (p<0.05) in both Defa 8 and β-defalp expression of sick newborn when compared with a group of young healthy alpacas raised in similar conditions in a previous study. The results showed that α- and β-enteric defensins are induced significantly during enteric diseases in alpacas.